Doppler‐Derived Renal Venous Stasis Index in the Prognosis of Right Heart Failure. Issue 21 (5th November 2019) - Husain‐Syed, Faeq; Birk, Horst‐Walter; Ronco, Claudio; Schörmann, Tanja; Tello, Khodr; Richter, Manuel J.; Wilhelm, Jochen; Sommer, Natascha; Steyerberg, Ewout; Bauer, Pascal; Walmrath, Hans‐Dieter; Seeger, Werner; et al.
Abstract : Background: Persistent congestion with deteriorating renal function is an important cause of adverse outcomes in heart failure. We aimed to characterize new approaches to evaluate renal congestion using Doppler ultrasonography. Methods and Results: We enrolled 205 patients with suspected or prediagnosed pulmonary hypertension (PH) undergoing right heart catheterization. Patients underwent renal Doppler ultrasonography and assessment of invasive cardiopulmonary hemodynamics, echocardiography, renal function, intra‐abdominal pressure, and neurohormones and hydration status. Four spectral Doppler intrarenal venous flow patterns and a novel renal venous stasis index (RVSI) were defined. We evaluated PH‐related morbidity using the Cox proportional hazards model for the composite end point of PH progression (hospitalization for worsening PH, lung transplantation, or PH‐specific therapy escalation) and all‐cause mortality for 1‐year after discharge. The prognostic utility of RVSI and intrarenal venous flow patterns was compared using receiver operating characteristic curves. RVSI increased in a graded fashion across increasing severity of intrarenal venous flow patterns ( P <0.0001) and was significantly associated with right heart and renal function, intra‐abdominal pressure, and neurohormonal and hydration status. During follow‐up, the morbidity/mortality end point occurred in 91 patients and was independently predicted by RVSI (RVSI in the third tertile versus referent: hazard ratio: 4.72 [95% CI, 2.10–10.59; P <0.0001]). Receiver operating characteristic curves suggested superiority of RVSI to individual intrarenal venous flow patterns in predicting outcome (areas under the curve: 0.789 and 0.761, respectively; P =0.038). Conclusions: We propose RVSI as a conceptually new and integrative Doppler index of renal congestion. RVSI provides additional prognostic information to stratify PH for the propensity to develop right heart failure. Clinical Trial Registration: URL: https://www.clinicaltrials.gov/ . Unique identifier: NCT03039959.